Determinants of Taxpayer Compliance at KPP Pratama Sumbawa Besar During the Covid-19 Pandemic - Ni Made Ulantari; Putu Kepramareni; AA. Ketut Budiastra (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
Taxpayer compliance of KPP Pratama Sumbawa Besar, in terms of timely reporting of Annual Income Tax Returns submitted from 2019 to 2021, had not yet reached 100% of the realization target in the form of the number of Taxpayers who are required to submit Annual Income Tax Returns. Therefore, the research was conducted to measure the influence of the determinants of taxpayer compliance at the KPP Pratama Sumbawa Besar during the COVID-19 pandemic. The determinants that are the independent variable in this study include the e-billing system, e-Filing/e-Form application, tax sanctions, tax knowledge, and awareness of taxpayers, and the dependent variable is taxpayer compliance. To achieve the research objectives, this research used a quantitative approach. The primary data were collected using a Likert scale questionnaire and a test instrument which were distributed to the respondents selected to be the population or sample for the study. Interviews were also conducted with the respondents to confirm their responses to the questionnaire. The Population or the sample serving as the secondary data source was taken from the data on the number of taxpayers registered at the KPP Pratama Sumbawa Besar who had been required to submit or report their Annual Income Tax Returns in 2021 using the e-Filing/e-Form facility. Based on the results of the analysis, there is a positive and significant influence of the e-billing system, e-Filing/e-Form application, tax sanctions, tax knowledge, and awareness of taxpayers on taxpayer compliance.